Nickel oxide optimization using Taguchi design for hydrogen detection. (5th July 2018) - El khalidi, Zahira; Hartiti, Bouchaib; Fadili, Salah; Thevenin, Philippe
Abstract: In this work, we established Taguchi's design of experiment as a statistical tool to decrease the amount of experiments, providing the practical optimal condition to operate a chemical sensor with high sensing quality. The main idea is to maximize the signal-to-noise "higher is better", based on the optimization of texture coefficient extracted from XRD data using L9 (3 3 ) orthogonal array, with three factors (concentration of NiO precursor, annealing temperature and annealing time). The process parameters are then varied in order to specify the best deposition parameters to obtain optimal texture coefficient of NiO thin films adopted for best oxidation/reduction reactions. After the calculation of S/N ratio based on the texture coefficient, we controlled the concentration and the annealing time to have good structural properties. The factors combination are (A3 B1 C1 ) corresponding respectively to the concentration [Ni 2+ ] = 0.08 M, the temperature T = 380 °C and the annealing time about 3 min. These factors are considered as the best combination of process parameters that leads to the optimal texture coefficient of NiO thin films. The gas testing was made on the sample with optimal conditions. This sample showed very low grain sizes with a film thickness equal to (380 nm). The gas testing under H2, acetone and ethanol revealed a high conductance, with a response of 55, at the concentration of 500 ppm with T = 300 °C. Graphical abstract: Highlights: Elaboration of Taguchi design of experiments with L9 (3) 3 orthogonal array. Our sample shows good crystal sizes, morphology and texture. NiO showed high response of 55 under H2, at 500 ppm and T = 300 °C.